2020
DOI: 10.1016/j.compositesa.2020.105809
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bundle Simulation approach for the compression molding process of Sheet Molding Compound

Abstract: The manufacturing process of Sheet Molding Compounds (SMC) induces a reorientation of fibers during the flow, which influences local properties and is of interest for structural computations. Typically, the reorientation is described with an evolution equation for the second order fiber orientation tensor, which requires a closure approximation and multiple empirical parameters to describe long fibers. However, CT scans of SMC microstructures show that fiber bundles stay mostly intact during molding. Treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Only the highly sheared strands are more likely to fan out. This observation justifies the simplifying assumption to represent thousands of carbon fibers within a strand as one bundle in order to shorten the calculation time and to enable full component scale simulations [73].…”
Section: Direct Bundle Simulation (Dbs)mentioning
confidence: 68%
See 4 more Smart Citations
“…Only the highly sheared strands are more likely to fan out. This observation justifies the simplifying assumption to represent thousands of carbon fibers within a strand as one bundle in order to shorten the calculation time and to enable full component scale simulations [73].…”
Section: Direct Bundle Simulation (Dbs)mentioning
confidence: 68%
“…This simplification method reduces the numerical calculation time by representing thousands of fibers as fiber bundles. Considering microstructure studies reported in the literature [4,73,103,104], it can be seen that most of the fiber bundles or strands widen and flatten, but do not disperse. Only the highly sheared strands are more likely to fan out.…”
Section: Direct Bundle Simulation (Dbs)mentioning
confidence: 97%
See 3 more Smart Citations